Rapid and manual-shaking exfoliation of amidoximated cellulose nanofibrils for a large-capacity filtration capture of uranium. Issue 14 (8th March 2022) - Zhang, Weihua; Han, Xiao; You, Jun; Zhang, Xiaofang; Pei, Danfeng; Willför, Stefan; Li, Mingjie; Xu, Chunlin; Li, Chaoxu
Abstract : Rapid and high-efficiency exfoliation of cellulose nanofibrils for capturing uranium ions with high capacity in a continuous filtration flow. Abstract : The efficient extraction of the aquatic uranium element has drawn growing research interest because of its importance for both nuclear energy acquirement and water environmental remediation. Large-capacity, rapid filtration adsorption is promising, but remains challenging in capturing aquatic uranium ions. Herein, cyanoethyl substitution was found to enable the rapid exfoliation of cyanoethyl cellulose nanofibrils by mild shear ( e.g., manual shake and homogenization) within 30 min with a conversion of up to ∼90% and unique re-dispersibility in many organic solvents. After hydrolyzing cyanoethyl into amidoxime, the resultant amidoximated cellulose nanofibrils, serving as a novel type of green absorbent, exhibited rapid kinetics (<5 min) and large reversible capacity (1327 mg g −1 ) in aquatic uranium adsorption. Their rigid fibrous feature and super dispersibility facilitated the construction of fibrous porous films to capture uranium ions in high capacity in continuous filtration flow. Therefore, this cyanoethyl exfoliation may not only provide an unprecedented route for the rapid and energy-efficient production of cellulose fibrils, but also promises a green and sustainable alternative for the high-efficiency extraction of aquatic uranium element.